The role of elastography in thyroid ultrasonography. Issue 5 (October 2016) - Magri, Flavia; Chytiris, Spyridon; Chiovato, Luca
Abstract : Purpose of review: Elastography is a novel noninvasive diagnostic tool that is helpful in the evaluation of thyroid nodules. The purpose of this review is to provide a comprehensive summary of the use of elastography in the clinical thyroid setting. Recent findings: Initial and subsequent studies show that elastography has both a sensitivity and specificity that approaches 100% for the determination of thyroid cancer within a thyroid nodule. In addition, the technique also has a very high negative predictive value and thus, may also be helpful in identification of thyroid nodules that do not need further diagnostic evaluation, including fine-needle aspiration biopsy. These characteristics also apply to both strain and shear wave elastography. However, as both the extent of tissue compression and the operator's classification of a nodule using a qualitative color code are subjective, intra and interobserver variability is an important reason for some conflicting findings. Summary: Elasticity within a thyroid nodule, as evaluated by elastography, offers diagnostic results that are equal to or sometimes even greater than that of conventional ultrasonography for the determination of thyroid malignancy. The integration of both techniques in the clinical work-up of thyroid nodules can thus significantly improve the accuracy of the diagnosis of thyroid nodules.